Antioxidant Activity in Rheum emodi Wall (Himalayan Rhubarb) - Park, Sang Koo (Molecules, 2021)
Using natural products as antioxidant agents has been beneficial to replace synthetic products. Efforts have been made to profile the antioxidant capacities of natural resources, such as medicinal plants. The polyphenol content of Himalayan rhubarb, Rheum emodi wall, was measured and the antioxidant activity was determined using DPPH and ABTS(+) assay, and the oxidative stress was assessed using SOD enzymatic assay. Five different solvent fractions, n-hexane, n-butanol, ethyl acetate, dichloromethane, and water, were used for screening the antioxidant capacity in effort to determine the optimum extraction solvent. The total phenolic contents for R. emodi fractions ranged from 27.76 to 209.21 mg of gallic acid equivalents (GAE)/g of dry weight. DPPH and ABTS(+) assay results are presented into IC(50) values, ranged from 21.52 to 2448.79 μg/mL and 90.25 to 1718.05 μg/mL, respectively. The ethyl acetate fraction had the highest antioxidant activity among other fractions. Also, n-butanol and water fractions showed significantly lower IC(50) values than the positive control in DPPH radical scavenging activity. The IC(50) values of SOD assay of fractions ranged from 2.31 to 64.78 μg/mL. A similar result was observed with ethyl acetate fraction showing the highest SOD radical scavenging activity. The study suggests that the ethyl acetate fraction of R. emodi possess the strongest antioxidant activity, thus the most efficient in extracting antioxidant contents. Moreover, a highly significant correlation was shown between total polyphenol content and antioxidant activity screening assays. The compounds related to the antioxidant activity of R. emodi were identified to myricitrin, myricetin 3-galloyl rhamnoside, and myricetin, which have not been reported in studies about R. emodi before.